Analisis Persepsi Penonton Terhadap Sinetron Magic 5 Indosiar - Nur, Galuh Fitriani (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
Based on the background, to facilitate the conduct of research, the focus of this research is to see how the audience's perception of the soap opera “Magic 5 Indosiar” and also the positive and negative impacts of the soap opera “Magic 5 Indosiar”. The purpose is to find out the audience's perception of the soap opera “Magic 5 Indosiar” and to find out the positive impact and also the negative impact obtained in the movie “Magic 5 Indosiar” based on Stuart Hall's theory: Encoding/Decoding. To identify these problems thoroughly, the researcher used a qualitative method with a descriptive approach. The researcher then conducted observation and documentation in the research. The data obtained then on the shows contained in television researchers want to take a show about the movie “Magic 5 Indosiar” which is a teenage fantasy drama genre. The program is able to attract the attention of the audience, especially among teenagers. Through this research, it is hoped that it can choose good viewing and provide positive benefits. So that the method used is a qualitative method with a descriptive approach. The results of this study indicate that the public perception is that there is actually an element of education presented by this soap opera that teaches us to help and protect fellow brothers even though they are not siblings. In the age field, usually more mature people see from the conflict side of the problem to how to solve it.